Epithelial-to-mesenchymal transition (EMT) causing acquired resistance to afatinib in a patient with epidermal growth factor receptor (EGFR)-mutant lung adenocarcinoma - Chai, Chee Shee; Poh, Mau Ern; Liam, Chong Kin; Pathmanathan, Rajadurai (AME Publishing Company, 2018)
We report the first case of epithelial-to-mesenchymal transition (EMT) as the cause of acquired resistance to the second-generation EGFR-tyrosine kinase inhibitor (TKI), afatinib in a patient with advanced non-small cell lung cancer (NSCLC) harboring a sensitizing EGFR mutation. Patients with EGFRmutant NSCLC inevitably develop acquired resistance while on EGFR-TKI treatment. EMT which renders cancer cells more invasive and migratory is one of the mechanisms of acquired resistance to EGFR-TKIs and correlates with a poor prognosis. Possible therapeutic strategies in patients with EMT include blocking M2 muscarinic receptor signalling, targeting EMT with histone deacetylase inhibitors such as entinostat and MEK-inhibitors such as selumetinib, inhibition of microRNAs, immunotherapy and inhibiting fibroblast growth factor receptor-1.